Animals as specific objects of obligations under Polish and German law (Volume 46, Edition 1) - Lubelska-Sazanów, Małgorzata (2021)
Defining where the needs of contracting parties end, and where the mistreatment of animals begins is especially difficult in contract law, where protecting animals is not a basic premise. Thus, although animal law is a widely discussed topic, the position of animals under civil law has not been discussed comprehensively before. The first chapters of the book set the background for subsequent civil law considerations given that the object of a contractual obligation is an animal, and the impact this has on the conclusion, performance and consequences of non-performance of a contract. It constitutes a unique interdisciplinary and comparative work focused mainly on animals in contractual relations (e.g. sale, donation, lease, tenancy, commission, agency, safe-keeping, training contracts).